1999
DOI: 10.3109/17453679908997818
|View full text |Cite
|
Sign up to set email alerts
|

3D-radiographic analysis does not improve the Neer and AO classifications of proximal humeral fractures

Abstract: The Neer and AO fracture classifications for fractures of the proximal humerus have shown poor reproducibility based on plain radiography. We wanted to investigate whether the addition of 3-dimensional (3D) reconstructions would increase the reproducibility of classification. 7 observers independently classified 24 fractures of the proximal humerus using both plain radiographs, CT and 3D and the classification was repeated 2 months later. There was a moderate interobserver agreement when using the Neer classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 18 publications
(14 reference statements)
0
53
1
2
Order By: Relevance
“…Bernstein et al [2] reported a mean kappa value of 0.52. No significant improvement of mean kappa values has been demonstrated despite exclusive use of high-quality radiographs [2,13] or by adding CT scans and three-dimensional reconstructions [2,12,15,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bernstein et al [2] reported a mean kappa value of 0.52. No significant improvement of mean kappa values has been demonstrated despite exclusive use of high-quality radiographs [2,13] or by adding CT scans and three-dimensional reconstructions [2,12,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…1) of proximal humeral fractures is commonly used. Several previous studies have shown poor agreement between observers using the system [1,2,3,9,12,13,14,15,16]. Low agreement might explain conflicting study outcomes of the treatment of three-and four-part fractures [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28][29][30] Because important new concepts for prognosis and treatment of PHF do not easily fit in past classification systems, some authors have proposed new imaging techniques 8,12 or new functional classifications. 14 Since 2003, new systems of fracture classifications have been published. 20,22,31,32 Hertel 22 presented a structured system for reading images, including 12 questions, which require 3-D image measurements.…”
Section: Background On the Diagnosis And Classification Of Phfmentioning
confidence: 99%
“…Such difference towards classifications' agreement could be due to multiple variables, for example, studies of low quality because of difficulties in placing patients with a fracture of proximal humerus, and also the surgeon's lack of experience to analyze these fractures (5)(6)(7)(8)(9)(10) . In spite of improvements demonstrated by some authors in the agreement of intra-and interobserver results using more complex tests like simple tomography and tridimensional (3D) reconstructions, these results are inconclusive when the relationship between classifications and suggestions of treatment is evaluated towards physician's experience (7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%